Evaluation of the Antibiotic Properties of Probiotics and their Efficacy on Performance and Immune Response in Broiler Chicken - Ngunyangi , E.N.; Tuitoek, J.K.; Ambula, M.K.; Wachira, A.M. (International Journal of Poultry Science, 2019)
Objective: The study aimed to evaluate the extent of use of probiotics in the poultry feed industry and their efficacy in broiler diets. Methodology: Two surveys involving 100 agro vets and 36 poultry farmers were carried out. Fifteen brands of probiotics 0were found in agro vets with Product 1, 2, 3 and Product 4 being common. A total of 74.4% of the farmers used probiotics and Product 1, 7, 2 and Product 4 were common. Three hundred and seven, day-old broiler chicks were randomly assigned to dietary treatments; Control diet, Diet 2 (Product 1), Diet 3 (Control+Product 4), Diet 4 (Control+Product 7) and Diet 5 (Product 2). Disk diffusion test was used to test the inhibitory effect of probiotics on bacteria cultures; Escherichia coli, Staphylococcus aureus, Bacillus cereus and Candida albicans. Results: Probiotics had no significant effect (p>0.05) on daily weight gain, feed intake and feed conversion ratio during starter phase. Performance was not significantly affected by probiotics during the finisher phase except for Product 2 which depressed growth. Blood samples were collected to test the effects of probiotics on antibody response to Infectious Bursal Disease virus and they had no significant effect (p = 0.6868). Product 4 and 7 had an inhibitory effect while Product 1 and 2 did not. Conclusion: Performance of broilers was not affected by the inclusion of probiotics in the diet.